Caracterização química e atividade leishmanicida dos extratos hidroetanólicos de própolis vermelha e Dalbergia ecastophyllum (FABACEAE) - Araujo, Jaltaira Montalvão Etinger de (2014)
Leishmania is the etiological agent of leishmaniasis. are protozoan trypanosomes genus, obligatory intracellular parasite of the phagocytic system cells mononuclear, with a flagellate form (promastigote), found in the intestinal tract of the insect vector and other intracellular aflagellate (amastigote). In leishmaniasis chemotherapy, pentavalent antimonial are used as first choice drugs. Other drugs such as pentamidine and amphotericin B have been used as alternative drugs. However, these drugs require parenteral administration in the long-term and exhibit serious side effects. Thus, the high toxicity, costs and associated resistance treatments available make it increasingly a search for new substances which can be used in therapy, especially those obtained from natural sources. The objective of this study was to evaluate the chemical profile and the leishmanicide effect in vitro red propolis extracts and Dalbergia ecastophyllum in promastigotes forms of Leishmania chagasi and Leishmania amazonensis. Red Propolis samples and Dalbergia ecastophyllum were collected in the low São Francisco River in Sergipe state, Brazil. The chemical characterization of hydroethanolic extract of propolis was made by Reverse Phase High-performance liquid chromatography (HPLC-FR). Leishmanicidal effect of red propolis extracts and D. ecastophyllum were made in promastigotes of Leishmania chagasi and Leishmania amazonensis by using the Alamar Blue staining method. The cytotoxicity of the propolis extract was evaluated in human macrophages J774 line using the MTT method. By chemical analysis could be identified in red propolis extracts the following phenolic compounds: Vanillic Acid, Ferulic Acid, Rutin, Isoliquiritigenin, Formononetin and Biochanin A, whereas the D. ecastophyllum extract were identified: vanillic acid, Isoliquiritigenin, Formononetin and Biochanin A. As the viability assessment, the obtained ICs50 for red propolis were: 21.54 μg/mL for L. chagasi and 9.73μg/mL for L. amazonensis. For the extract of D. ecastophyllum the ICs50 obtained were 70.47 μg/mL for L. chagasi and 53.42 μg/mL for L. amazonensis. The CC50 of propolis extract in macrophages was 72.63 μg/mL. These results show that the red propolis extract of the low São Francisco has the D. ecastophyllum as botanical origin and it presents leishmanicide potential, with low toxicity.